Cellular imaging of human atherosclerotic lesions by intravascular electric impedance spectroscopy - Streitner, Ines; Borggrefe, Martin; Süselbeck, Tim; Streitner, Florian (PLOS ONE, 2012)
Background: Newer techniques are required to identify atherosclerotic lesions that are prone to rupture. Electric impedance spectroscopy (EIS) is able to provide information about the cellular composition of biological tissue. The present study was performed to determine the influence of inflammatory processes in type Va (lipid core, thick fibrous cap) and Vc (abundant fibrous connective tissue while lipid is minimal or even absent) human atherosclerotic lesions on the electrical impedance of these lesions measured by EIS. Methods and Results: EIS was performed on 1 aortic and 3 femoral human arteries at 25 spots with visually heavy plaque burden. Severely calcified lesions were excluded from analysis. A highly flexible micro-electrode mounted onto a balloon catheter was placed on marked regions to measure impedance values at 100 kHz. After paraffin embedding, visible marked cross sections (n = 21) were processed. Assessment of lesion types was performed by Movats staining. Immunostaining for CD31 (marker of neovascularisation), CD36 (scavenger cells) and MMP-3 (matrix metalloproteinase-3) was performed. The amount of positive cells was assessed semi-quantitatively. 15 type Va lesions and 6 type Vc lesions were identified. Lesions containing abundant CD36-, CD31- and MMP-3-positive staining revealed significantly higher impedance values compared to lesions with marginal or without positive staining (CD36+455±50 Ω vs. CD36- 346±53 Ω, p = 0.001; CD31+436±43 Ω vs. CD31- 340±55 Ω, p = 0.001; MMP-3+ 400±68 Ω vs. MMP-3- 323±33 Ω, p = 0.03). Conclusions: Atherosclerotic lesions with abundant neovascularisation (CD31), many scavenger receptor class B expressing cells (CD36) or high amount of MMP-3 immunoreactivity reveal significantly higher impedance values compared to lesions with marginal or no detection of immunoreactivity. Findings suggest that inflammatory processes in vulnerable plaques affect the impedance of atherosclerotic lesions and might therefore be detected by EIS.